Light-cone analysis of the pure spinor formalism for the superstring - Berkovits, Nathan [UNESP]; Jusinskas, Renann Lipinski [UNESP] (Springer, 2014)
Physical states of the superstring can be described in light-cone gauge by acting with transverse bosonic alpha(j)(-n) and fermionic q(-n)(-a) operators on an SO(8)-ovariant superfield where j,a = 1 to 8. In the pure spinor formalism, these states are described in an SO(9,1)-covariant manner by the cohomology of the BRST charge Q = 1/2 pi i closed integral lambda(alpha)d(alpha). In this paper, a similarity transformation is found which simplifies the form of Q and maps the light-cone description of the superstring vertices into DDF-like operators in the cohomology of Q.
Keywords: Superstrings and Heterotic Strings; BRST Symmetry